Capture Region of Tactical Missile Equipped With Semi-Active Laser Seeker Using Tobit Kalman Filter - Youngjun Lee; Sangmin Lee; Youdan Kim; Yongsu Han; Jangseong Park; Gyeong-Hun Kim (IEEE Access)
A Tobit Kalman filter-based guidance system was proposed for expanding the capture region of missiles with a strapdown semiactive laser seeker. The characteristics of the semiactive laser seeker were analyzed, and the narrow field-of-view laser seeker model was used based on the analysis. A guidance filter was designed to utilize the saturated region of the seeker to overcome limited maneuverability arising from the narrow field-of-view range. A Tobit Kalman filter is adopted, and the prediction stage was modified so that the Tobit Kalman filter can be applied for nonlinear process models. The filter model for estimating the look angle, LOS angle, and LOS rate was formulated. The proposed guidance filter can estimate the state more robustly even if saturated measurements are given. This study showed that widening the available field-of-view range can lead to the expansion of the capture region. The impact angle control composite guidance and impact angle control guidance with bearing-only measurement were used for intercepting the target with the desired impact angle. Numerical simulations were performed to demonstrate the effectiveness of the proposed method in the saturated region of the seeker and show that the proposed method can expand the size of the capture region.